RIBONUCLEASE V OF ESCHERICHIA COLI, I. DEPENDENCE ON RIBOSOMES AND TRANSLOCATION - Kuwano, Michihiko (1969)
A new RNase activity, tentatively named RNase V, was found in cell-free extracts of E. coli. This activity requires ribosomes, G and T factors, tRNA, K(+) or NH(4)(+), Mg(2+), GTP, and a sulfhydryl compound to degrade poly U, poly A, T4 phage mRNA, or E. coli mRNA. RNase V is specific for mRNA; it does not attack ribosomal RNA. It is inhibited by antibiotics that decrease breakdown of mRNA in vivo, such as chloramphenicol and streptomycin, and by such agents as 5′-β, γ-methylene-guanosine triphosphate, and fusidic acid, which inhibit ribosome-dependent GTPase and translocation of ribosomes along mRNA. The evidence suggests that RNase V is either an integral part of the ribosome or is tightly associated with it, and that it selectively degrades mRNA in intact cells.